FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TEKNIK MENYUSUI PADA IBU NIFAS DI PMB ROSITA - Eka Maya Saputri; Juli Selvi Yanti (Ensiklopedia Research and Community Service Review, 2026)
The achievement of exclusive breastfeeding to date has not been encouraging. This is because mothers lack confidence that their breast milk is sufficient for their babies. Proper breastfeeding technique refers to the method of providing breast milk to an infant using appropriate positioning and practices. This technique can be taught to mothers while taking into account their individual circumstances and comfort. Providing counseling on breastfeeding techniques is crucial. It also helps prevent various common problems that can cause difficulties. Poor breastfeeding technique can reduce breast milk production, leading to infant weight loss and difficulties with nursing. Incorrect positioning and technique during breastfeeding can significantly affect the success of exclusive breastfeeding and lead to problems such as sore nipples and mastitis. The aim of this study is to identify the factors associated with breastfeeding techniques among postpartum mothers at PMB Rosita. This study employs a quantitative approach and is an analytical survey with a cross-sectional design. The results of this study show the following variables: age (p-value 0.032; 0.05), education (p-value 0.019; 0.05), occupation (p-value 0.006; 0.05), number of children (p-value 0.001; 0.05), knowledge (p-value 0.006; 0.05).It is concluded that all variables are associated with breastfeeding techniques among postpartum mothers. It is hoped that, following this study, mothers will be able to breastfeed their infants correctly, thereby ensuring their nutritional needs are adequately met.Keywords: Breastfeeding Techniques, Postpartum Period, PMB Rosita